THE ROLE OF FARMERS AND MIDDLEMEN IN THE PERSPECTIVE OF ACTOR NETWORK THEORY: STUDY OF ACTORS ON AGRICULTURAL PRODUCT DISTRIBUTION CHAIN IN KAPONAN VILLAGE, MAGELANG REGENCY, CENTRAL JAVA - Stefany Anindya Putri; Wardani Umi Maesyaroh; Arifah Arifah; Restina Lestari; Widhi Handayani (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2023)
The agricultural sector plays a role in encouraging the social, economic and trade sectors in Indonesia. However, the income of workers of the agricultural sector, especially farmers, is lower than in other sectors. In addition to the length of the distribution chain, farmers’ dependence on middlemen is also one of the factors responsible for the low income of farmers, including in Kaponan Village, Magelang Regency, Central Java Province. This study aims to (1) identify the actors involved in the distribution chain of agricultural products in Kaponan village and (2) explain the patterns of relationships between actors involved in the distribution chain of agricultural products in Kaponan Village. This research is a qualitative case study research involving eleven informants as primary data sources. The results showed that apart from the three main actors, namely farmers, farmer groups, and middlemen, there were other actors controlling access to sales of agricultural products to supermarkets, namely technology. The relationship between farmers and middlemen in Kaponan Village is a cooperative relationship that indicates a mutualistic relationship. The farmers in Kaponan Village did not feel disadvantaged by middlemen and this relationship does not create dependence, but they feel that middlemen help them provide access to sell their agricultural products.